2014
DOI: 10.1002/mabi.201400480
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Efficacy of Pluronic Copolymer Micelle Encapsulated SCR7 against Cancer Cell Proliferation

Abstract: 5,6-Bis(benzylideneamino)-2-mercaptopyrimidin-4-ol (SCR7) is a new anti cancer molecule having capability to selectively inhibit non-homologous end joining (NHEJ), one of the DNA double strand break (DSB) repair pathways inside the cells. In spite of the promising potential as an anticancer agent, hydrophobicity of SCR7 decreases its bioavailability. Herein the entrapment of SCR7 in Pluronic copolymer is reported. The size of the aggregates was determined by transmission electron microscopy (TEM) and dynamic l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

7
2

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 68 publications
0
34
0
Order By: Relevance
“…Since NHEJ inhibitors can block residual DSB repair following irradiation, this is considered as an ideal strategy to improve the efficacy of radiotherapy and, in some instances, chemotherapy. Previously, we showed that SCR7 could improve radio and chemosensitivity in mice tumor models and cancer cell lines . Interestingly, we noted that treatment with SCR7‐cyclized or SCR7‐pyrazine along with radiation resulted in elevated levels of DSBs, which was higher than either of the agents alone.…”
Section: Discussionmentioning
confidence: 88%
“…Since NHEJ inhibitors can block residual DSB repair following irradiation, this is considered as an ideal strategy to improve the efficacy of radiotherapy and, in some instances, chemotherapy. Previously, we showed that SCR7 could improve radio and chemosensitivity in mice tumor models and cancer cell lines . Interestingly, we noted that treatment with SCR7‐cyclized or SCR7‐pyrazine along with radiation resulted in elevated levels of DSBs, which was higher than either of the agents alone.…”
Section: Discussionmentioning
confidence: 88%
“…Cell cycle analysis was carried out as described previously 38, 39 . Initially, effect of 5g (0, 10, 20 and 30 µM) on Nalm6, REH, K562, Molt4, MCF7 and EAC cells were tested at 24 h time point.…”
Section: Methodsmentioning
confidence: 99%
“…Detection of γ-H2AX foci in Nalm6 and HeLa cells post 5g treatment was performed as described previously 39, 40 . In brief, cells (50,000/ml) were seeded on coverslips and treated with 5g (10 and 30 µM for 24 h), followed by harvesting and fixing of the cells using 4% paraformaldehyde for 10′ at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…In conjugation with DSB-inducing agents, SCR7 has tremendous therapeutic value in cancer cells and with respect to genome editing in normal cells [143,[145][146][147]. It was recently reported that SCR7 in an encapsulated form possesses five times more activity than the un-encapsulated drug [148,149].…”
Section: Repair Processesmentioning
confidence: 99%